(untitled) (International Journal of Environmental Sciences, 2025)
Social entrepreneurship has arisen as a crucial means of tackling societal issues, especially under the leadership of women entrepreneurs who integrate social objectives with commercial ambitions. Despite their increasing importance, the motivational elements that propel and maintain the effectiveness of women-led social companies remain insufficiently examined. This study examines the impact of five primary motivational factors like independence, satisfaction, earning, security, and recognition on the sustained performance of female social entrepreneurs. The study, conducted in the Chennai district, using a standardized questionnaire distributed to 230 women entrepreneurs listed in the MSME database. The analysis utilizing correlation and multiple regression indicates that satisfaction, earnings, security, and recognition have a significant positive influence on entrepreneurial performance, whereas independence exhibits a statistically significant negative effect. The model accounts for 74.7% of the variance in performance outcomes, highlighting the essential importance of incentive in maintaining social ventures. These results underscore the necessity of developing support networks that prioritize the enhancement of financial security, acknowledgment, and personal fulfilment, rather than advocating for autonomy in isolation. The study offers significant empirical insights into women’s social entrepreneurship and presents recommendations for policy and practice to improve the success and sustainability of women-led social enterprises.